Teacher Preparation by Universities: Internal Stakeholders Perception of Teacher Education Curriculum Content in Makerere and Kyambogo Universities - Kisige, Abdu; Ezati, Betty Akullu; Kagoda, Alice Merab (The Asian Institute of Research, Education Quarterly Reviews, 2021)
Developing a teacher education curricular content is an enduring concern for teacher educators. A continuous method to providing quality teacher education curriculum content discloses the potential for teacher educators to produce high-quality teachers. Drawing on data from twenty teacher educators and sixteen student teachers in public institutions in Uganda, this article explored the perceptions of the teacher education curriculum content held by academic staff and student teachers in public Universities in Uganda. Using Pedagogical Content Knowledge Model as a tentative model of teacher preparation and Constructivism theory as an interpretive framework, the study was guided by one objective namely: (1) to analyze the perception of internal stakeholders about teacher education curriculum content offered in Makerere and Kyambogo Universities. This research adopted a qualitative, multiple case study design that was anchored in the interpretivist paradigm and directed by the social constructivism thinking. Data were collected using semi-structured interviews were participants from twenty teacher educators and sixteen student teachers who were purposively and conveniently selected. It was therefore concluded that both lecturers and student teachers viewed teacher education curriculum content positively viewing it as enabling learners to be equipped with specialized teaching skills, essentially directed towards teaching profession. Thus, recommendations to improve the stakeholder perception of the teacher education curriculum content are made and these include: teacher education curriculum review and the need to design a 21st-century teacher education curriculum by teacher trainers in corroboration with other university units rendering a training service to teacher trainees. This would bridge the gap of the disjointed teacher education curriculum content at Makerere and Kyambogo Universities hence strengthening the building blocks that produce a teacher.
Keywords: Curriculum, Internal-Stakeholder, Pre-Service Teacher, Teacher Education